2015
DOI: 10.3389/fnagi.2015.00049
|View full text |Cite
|
Sign up to set email alerts
|

Anodal transcranial direct current stimulation of parietal cortex enhances action naming in Corticobasal Syndrome

Abstract: Background: Corticobasal Syndrome (CBS) is a neurodegenerative disorder that overlaps both clinically and neuropathologically with Frontotemporal dementia (FTD) and is characterized by apraxia, alien limb phenomena, cortical sensory loss, cognitive impairment, behavioral changes and aphasia. It has been recently demonstrated that transcranial direct current stimulation (tDCS) improves naming in healthy subjects and in subjects with language deficits.Objective: The aim of the present study was to explore the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 78 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…We identified 15 studies that evaluated the effects of tDCS on patients with Alzheimer’s disease [111], [112], [113], [114], [115], [116], Parkinson’s Disease [109], [117], [118], [119], [120], [121], Dementia with Lewy Bodies [122], Corticobasal degeneration [123], and Frontotemporal dementia [124]. In all, there were over 275 patients (some assigned to sham conditions) who received between 7 and 30 minutes of stimulation in each of 1 to 10 sessions with an intensity of between 1 and 2.8 mA.…”
Section: Tdcs Special Considerations For Safety In Aging Populationsmentioning
confidence: 99%
“…We identified 15 studies that evaluated the effects of tDCS on patients with Alzheimer’s disease [111], [112], [113], [114], [115], [116], Parkinson’s Disease [109], [117], [118], [119], [120], [121], Dementia with Lewy Bodies [122], Corticobasal degeneration [123], and Frontotemporal dementia [124]. In all, there were over 275 patients (some assigned to sham conditions) who received between 7 and 30 minutes of stimulation in each of 1 to 10 sessions with an intensity of between 1 and 2.8 mA.…”
Section: Tdcs Special Considerations For Safety In Aging Populationsmentioning
confidence: 99%
“…Although studies [13,[16][17][18][19][20][21] provide proof-of-concept for the efficacy of tDCS in PPA, these small studies do not yet provide sufficient evidence for sustainability of gains and generalization to untreated items. One difficulty in studying tDCS efficacy in PPA is its phenotypic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that a single session over the DLPFC was sufficient to strengthen episodic memory up to 1 month, relative to sham stimulation [95]. Similarly, DLPFC modulation showed beneficial memory effects in mild cognitive impairment (MCI) patients [97, 98], although these positive effects were obtained using different stimulation protocols (i.e., 10 excitatory sessions vs. 1 inhibitory session).…”
Section: Nibs and Dementiamentioning
confidence: 99%
“…Manenti et al [95] investigated the effect of atDCS on the DLPFC in individuals with subjective memory complaints, a condition at greater risk of AD [116]. Their findings showed that a single session over the DLPFC was sufficient to strengthen episodic memory up to 1 month, relative to sham stimulation [95].…”
Section: Nibs and Dementiamentioning
confidence: 99%